Políticas públicas de segurança e gestão carcerária: estudo sobre a criminalização da miséria no Sistema Penitenciário do Estado do Pará - SOUZA, Alexandre Samarone Silva de (Universidade Federal do Pará, 2011)
This research identifies as object the relation between criminalization and misery, the acts that lead the criminalization of the misery in the modern societies, focusing that this phenomenon has relation with the increase of the imprisonment of the characterized social segments of the needies. All the acts, action, speeches, tactics, strategies, perceptions, impressions, programs and projects had used as base to form on analysis more complete of this phenomenon. The image of the misery associated with crime is resulted of a daily pay-construction process, that strengthened with the common sense contributes to stigmatize the more vulnerable social segments of the society and also it masks the absence of public politics of assistance on the part of the governments that prevent the causes of reproduction of crime. Analyzing the discursive positions of some stratus of the society nuances of the perception can be understood multiple that if has of the criminals associates to the violence. The strategies and tactics of repression to crime that have extended the segregation to the segments most disfavored of the society on behalf of the defense of the public and economic order. This work has as purpose to understand the process of criminalization of the misery. One will be overcome as field of analyzes the Penitentiary System of the State of Pará, why the jail, as an institution of the system of public security, being always invoked as solution for the problem of crime, segregates the constructed profile of the taken criminal as threat the social order.